Biodistribution and persistence of human umbilical cord-derived mesenchymal stem cells in NCG mice: a comparative study - Guangyang Liu; Herui Wang; Xin Li; Yi Mi; Chenliang Zhang; Yaoyao Chen; Li Miao; Haomiao Long; Jun He; Qinggang Ge; Yongjun Liu (Future Science OA)
Introduction This study aims to investigate the biodistribution and persistence of human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) in NCG mice post-intravenous injection, utilizing 89Zr-PET/CT, bioluminescence imaging, multiplex immunohistochemistry (mIHC), and quantitative polymerase chain reaction (qPCR)Methods hUC-MSCs were labeled with 89Zr-oxine (89Zr-MSCs) or transduced with luciferase gene (Luc-MSCs). Real-time tracking of 89Zr-MSCs lasted for 14-days followed by mIHC staining of hCD73. Real-time tracking of Luc-MSCs lasted for 7-days, followed by mIHC staining of hCD73 and human Alu-based qPCR. All methods adhered to ICH and other regulatory guidelines for development of cell-based drugs.Results A biodistribution and persistence pattern was observed in the order of lung > liver > kidney > >spleen, although discrepancies were noted for the liver and kidney.Conclusion Each method exhibited strengths and weaknesses: 89Zr-PET/CT enabled long-term tracking but encountered issues with 89Zr shedding and dead cells; bioluminescence provided specific detection but was hampered by a rapid decline in signal; mIHC identified cells but relied on antigen abundance; qPCR detected minimal cell quantities but was unable to differentiate between live and dead cells. These limitations may obscure the true fate of cells in vivo, highlighting the need for more accurate and reliable assessment techniques.